Can whitening toothpastes maintain the optical stability of enamel over time? - da Silva, Eduardo Moreira (J Appl Oral Sci, 2018)
Besides the effects on the health of individuals, cigarette smoking can also interfere with the appearance of their teeth. OBJECTIVE: To evaluate the effect of cigarette smoking-toothbrushing-cycling (CSTC) with whitening toothpastes on the roughness and optical behavior of bovine enamel for eight weeks. MATERIAL AND METHODS: Thirty bovine dentin/enamel discs, 8.0 mm in diameter and 2.0 mm thick, were randomly divided into three groups according to the toothpastes: whitening (Colgate Luminous White - CW and Oral B 3D White - OW), and a non-whitening (Colgate - C). The roughness, color (CIE L*a*b* system), translucency and gloss were measured before and after the specimens were submitted to CSTC. The topography of the specimens was analyzed by scanning electron microscopy. During the first week, the specimens were daily subjected to the consumption of 20 cigarettes and brushed (40 strokes/100 g) with the toothpastes' slurries. Thereafter, the CSTC was weekly applied in an accumulated model (140 cigarettes/280 strokes) for seven weeks. The data were submitted to two-way ANOVA, Tukey's HSD test, and paired-t test (α=0.05). RESULTS: The three toothpastes produced significant changes in roughness, color, translucency and gloss (p<0.05). After eight weeks, the roughness and the gloss produced by the three toothpastes were similar (p>0.05), while OW produced the lowest color change and the translucency of C was lower than that of CW (p<0.05). The three toothpastes produced a significant decrease in L* values and a significant increase in a* values after eight weeks (p<0.05). No significant difference in the b* coordinate was found for OW (p=0.13) There were topographic changes in the enamel surfaces. CONCLUSIONS: The whitening toothpastes increased the roughness, changed the topography and were not able to maintain the optical stability of enamel exposed over eight weeks.